Attitudes, Ideological Associations and the Left–Right Divide in Latin America - Wiesehomeier, Nina; Doyle, David (Sage, 2012)
Do Latin American citizens share a common conception of the ideological left–right distinction? And if so, is this conception linked to individuals’ ideological self-placement? Selecting questions from the 2006 Latinobarómetro survey based on a core definition of the left–right divide rooted in political theory and philosophy, this paper addresses these questions. We apply joint correspondence analysis to explore whether citizens who relate to the same ideological identification also share similar and coherent convictions and beliefs that reflect the ideological content of the left-right distinction. Our analysis indicates that theoretical conceptions about the roots of, and responsibility for, inequality in society, together with the translation of these beliefs into attitudes regarding the state versus market divide, distinguish those who self-identify with the left and those who self-identify with the right.
Keywords: 59 Ciencia Política::5905 Vida política; ODS 10 - Reducción de las desigualdades